Analisis Kualitas Website Politeknik Negeri Medan - Sarah Rouli Tambunan; Annalisa Sonaria Hasibuan (Mahesa Research Center, 2022)
This article aims to analyze the quality of Politeknik Negeri Medan (Polmed) website. The problem is focused on the quality of the website as a means of information for the public both internally and externally. In order to approach the problem, the WebQual theory reference is used which measures the quality of the website based on three dimensions, namely: usability, information quality and interaction service. Data were collected through questionnaires filled out by 100 Politeknik Negeri Medan students. This research is a descriptive research with a quantitative approach. The results of the study concluded that usability and the information quality were in the good category. However, more improvements need to be made so that the website assessment becomes very good. What can be done is to fill in some information related to the study program that is still vacant and to update the information more intensely. Meanwhile, in terms of service interaction, it is still in the sufficient category because respondents several times still experience trouble when accessing the Polmed website. Another weakness is that there is no communication space on the website such as a chat column, suggestion box and criticism as a medium to communicate directly with institutions.